Genetic relatedness of Gram-negative bacteria colonizing gut and skin of neonates and mother's own milk. (November 2018) - Parm, Ülle; Štšepetova, Jelena; Eelmäe, Imbi; Merila, Mirjam; Ilmoja, Mari-Liis; Metsvaht, Tuuli; Lutsar, Irja; Soeorg, Hiie
Abstract Objective We described colonization of mother's own milk with Gram-negative bacteria and its relationship with neonatal colonization. Study Design Gram-negative bacteria isolated from weekly collected stool, skin and mother's own milk of hospitalized preterm (n  = 49) and healthy term neonates (n  = 20) were genotyped. Colonization-related factors were determined by logistic regression. Results Gram-negative bacteria were isolated from mother's own milk of 22.4% (n  = 11) and 15% (n  = 3) of mothers of preterm and term neonates, respectively. According to pulsed-field gel electrophoresis genetically similar strains were present in mother's own milk and gut of 8.2% (n  = 4) of mother–preterm neonate, but none of mother–term neonate pairs. In three of four late-onset sepsis caused by Gram-negative bacteria, colonization of gut, but not mother's own milk, with invasive species preceded late-onset sepsis. Conclusions Colonization of mother's own milk with Gram-negative bacteria is uncommon and transmission to neonatal gut may occur in less than one-tenth of neonate–mother pairs.